120 Gb/s all-optical NAND logic gate using reflective semiconductor optical amplifiers. Issue 12 (11th July 2020) - Kotb, Amer; Guo, Chunlei
Abstract : In this paper, the unique features of the reflective semiconductor optical amplifiers (RSOAs) are exploited to numerically simulate the ultrafast performance of an all-optical NOT-AND (NAND) logic gate for the first time using a return-to-zero modulation format at a data rate of 120 Gb/s. A comparison is made between RSOAs and conventional SOAs through studying the dependence of the gate's quality factor (QF) on the critical operational parameters, including the effects of both amplified spontaneous emission and operating temperature to get more realistic results. The results show that the all-optical NAND logic gate can be executed at 120 Gb/s using the RSOAs scheme with a higher QF than when using conventional SOAs.